Examining the Educational Benefits of Interacting with International Students - Luo, Jiali; Jamieson-Drake, David (Journal of International Students, 2013)
Through the analysis of alumni survey data from three graduating cohorts, this study examined the influence of interaction with international students on domestic students’ college outcomes and explored factors that helped to promote international interaction on college campuses. The findings indicate that in comparison to non-interactive domestic students, highly interactive domestic students reported significantly higher levels of development in a wide range of areas across the three cohorts. Also, the findings suggest that active engagement in college activities, such as coursework outside the major, contact with faculty outside class, ethnic or cultural clubs or organizations, and visiting speakers, was likely to promote interaction across cultures.